Thermal spraying composite ceramic powder material as well as preparation method and application thereof

By thermal spraying composite ceramic materials, using multiple loss mechanisms of various electromagnetic functional materials, the existing electromagnetic functional materials have solved the problems of narrow absorption frequency band, poor temperature resistance and poor bonding strength, and achieved efficient electromagnetic wave absorption and improved mechanics performance.

CN119462116AActive Publication Date: 2025-02-18AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510058808.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-02-18
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The narrow absorption frequency band, poor temperature resistance and cohesive bonding strength of existing electromagnetic functional materials lead to poor binding force with the substrate, which is easy to fall off, affecting the electromagnetic wave absorption efficiency and service life.

Method used

Thermal spray-coated composite ceramic materials, including matrix materials such as mullite, zirconia, etc., and functional materials such as SiBCNFe, Ti3SiC2, CNTs, etc., are used to prepare composites with multiple loss mechanisms through spray granulation, sintering and plasma spheroidization. Ceramic powder material improves its absorption and mechanical properties to electromagnetic waves.

Benefits of technology

The electromagnetic wave absorption frequency band is widened, the absorption loss is improved, the electromagnetic function is enhanced, the mechanical properties of the coating and the bonding strength with the substrate are improved, the porosity of the coating is reduced, and the service life is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462116A_ABST
    Figure CN119462116A_ABST
Patent Text Reader

Abstract

The invention relates to a thermal spraying composite ceramic powder material as well as a preparation method and application thereof, belongs to the technical field of high-temperature electromagnetic functional ceramic materials, and solves the problems that an existing electromagnetic functional material is narrow in absorption frequency band, low in absorption loss, poor in temperature resistance, poor in cohesive bonding strength, poor in bonding force with a substrate and easy to fall off. The composite ceramic material comprises a base material and a functional material, the base material is mullite and the like, and the functional material comprises SiBCNFe, Ti3SiC2, CNTs, MoSi2, ZnO and YSZ. The multifunctional material has multiple loss mechanisms, widens the electromagnetic wave absorption frequency band, improves the absorption loss and undertakes the controllability of the electromagnetic function; by controlling the size, density and sphericity of the material, the cohesive bonding strength and fluidity of the material are improved, the porosity of the prepared coating is reduced, and the compactness and mechanical property of the coating are improved; in addition, the various electromagnetic functional materials are temperature-resistant materials, so that the expansion of a preparation process and an application environment of the composite ceramic material is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of high-temperature electromagnetic functional ceramic materials, and in particular to a thermal spraying composite ceramic powder material and a preparation method and application thereof. Background Art

[0002] With the advancement of science and technology, electromagnetic waves are increasingly widely used, which not only endangers human health and interferes with the normal use of equipment, but also becomes increasingly diverse as a means of detection. Correspondingly, higher requirements are placed on materials for interference, shielding and absorption of electromagnetic waves. The application environment of electromagnetic functional materials is becoming more and more harsh. In practical applications, they are required to have adjustable electromagnetic functions to adapt to environmental changes.

[0003] At present, a single electromagnetic functional material and its loss mechanism limit its absorption performance of electromagnetic waves. Its absorption band is often narrow and its absorption loss is limited, which cannot meet the use requirements. To address this problem, people are committed to studying composite electromagnetic absorption materials composed of multiple electromagnetic functional materials, increasing the material's loss mechanism for electromagnetic waves and broadening the absorption band.

[0004] However, in practical applications, the electromagnetic functional coating composed of composite electromagnetic absorption materials has poor mechanical properties and low bonding strength (~6MPa). When the environment changes, including ambient temperature, medium and other factors, the coating is prone to cohesive fracture. Especially under harsh conditions of use, the coating is prone to problems such as shedding and failure, which affects the electromagnetic wave absorption efficiency and service life.

[0005] Therefore, it is necessary to find an electromagnetic functional material with excellent performance in many aspects, including temperature resistance, electromagnetic wave absorption bandwidth and bonding strength with the substrate, so as to adapt to the higher requirements for electromagnetic wave absorption materials put forward by increasingly complex application conditions. Summary of the invention

[0006] In view of the above analysis, an embodiment of the present invention aims to provide a thermal spray composite ceramic powder material and a preparation method and application thereof, so as to solve at least one of the problems of existing electromagnetic functional materials, namely, narrow absorption band, poor temperature resistance, and poor cohesive bonding strength resulting in poor bonding with the substrate and easy falling off.

[0007] In the first aspect, an embodiment of the present invention provides a thermal spraying composite ceramic material, which includes a matrix material and a functional material, wherein the matrix material is at least one of mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride, and the functional material includes SiBCNFe and / or SiCuCN, Ti3SiC2 and / or TiC, CNTs and / or carbon fiber, MoSi2 and / or Si3N4, ZnO and / or MnO2, and YSZ, and the functional material is uniformly dispersed in the matrix material.

[0008] Furthermore, in terms of mass percentage, the contents of the components in the composite ceramic material are: SiBCNFe 8%-10%, Ti3SiC2 15%-18%, CNTs 2%-5%, MoSi2 5%-8%, ZnO 4%-6%, YSZ 22%-27%, and the remainder mullite.

[0009] Furthermore, the composite ceramic material is a spherical powder with a particle size of 25-110 μm.

[0010] Furthermore, the bulk density of the spherical powder is 0.4-2.2 g / cm 3 , fluidity is 30-50s / 50g.

[0011] In a second aspect, an embodiment of the present invention provides a method for preparing the composite ceramic material, the method comprising: (1) According to the composition of the composite ceramic material, a matrix raw material, a functional raw material, deionized water and a binder are mixed to obtain a mixed slurry; (2) spray granulating the mixed slurry to obtain agglomerated powder; (3) sintering the agglomerated powder; (4) The powder sintered in step (3) is subjected to plasma spheroidization treatment and sieved.

[0012] Furthermore, in step (1), the mass of deionized water is 1-1.2 times the mass of the raw material.

[0013] Furthermore, the mass of the binder is 0.5-1% of the mass of the raw material.

[0014] Furthermore, in step (2), the process parameters of the spray granulation are: inlet temperature 340-350°C, outlet temperature 100-110°C, spray disk speed 30-40Hz, and feed speed 35-45rpm.

[0015] Furthermore, in step (3), the sintering process parameters are: sintering at 550-950°C for 2-4h under a protective atmosphere; sintering at 1100-1500°C for 2-5h.

[0016] Furthermore, in step (4), the process parameters of the plasma spheroidization treatment are: current 600-650A, main gas Ar 100-110SCFH, auxiliary gas H2 7-9SCFH, carrier gas Ar 8-10SCFH, powder feeding rate 2.0-3.0r / min.

[0017] In a third aspect, an embodiment of the present invention provides a high-temperature electromagnetic functional coating, which includes a functional layer, and the material of the functional layer includes the thermal sprayed composite ceramic material described in the first aspect or the thermal sprayed composite ceramic material obtained by the preparation method described in the second aspect.

[0018] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1. The present invention evenly disperses a variety of electromagnetic functional materials into the matrix material. The various electromagnetic functional materials have a variety of loss mechanisms, broaden the electromagnetic wave absorption band, improve the absorption loss, and assume the controllability of electromagnetic functions; for example, SiBCNFe and SiCuCN have magnetic loss and dielectric loss mechanisms, CNTs and carbon fibers have resistance loss mechanisms, and Ti3SiC2, MoSi2, ZnO, TiC, Si3N4, AlN, and MnO2 have dielectric loss mechanisms; In addition, the various electromagnetic functional materials are all temperature-resistant materials, which is conducive to the expansion of the preparation process and application environment of the composite ceramic material of the present invention.

[0019] 2. The various electromagnetic functional materials used in the present invention cooperate and coordinate with each other to play a role in broadening the electromagnetic wave absorption band. In addition to limiting the composition of the composite ceramic material, the present invention also limits the content of each component; the composite ceramic material not only achieves the broadening of the electromagnetic wave absorption band by increasing the loss mechanism, but also takes into account that the different physical and chemical properties of different electromagnetic functional materials may affect the morphology, structure and performance of the composite ceramic material obtained after combination, thereby affecting its electromagnetic function and service life in practical applications. The present invention needs to limit the content of the components.

[0020] 3. The present invention defines the composite ceramic material as a spherical powder with good fluidity and compactness, wherein the bulk density of the composite ceramic powder is 0.4-2.2 g / cm 3 The fluidity is 30-50s / 50g, which is beneficial to reduce the porosity of the prepared coating and improve the mechanical properties of the coating; in addition, the particle size and uniformity of the spherical powder will affect the density and bonding strength of the prepared coating. The particle size of the composite ceramic powder of the present invention is 25-110μm. The ceramic powder with a particle size in this range can make the coating have better bonding strength and lower porosity, and in the thermal spraying process, it can also reduce the evaporation loss of elements and improve the protective performance and service life of the coating.

[0021] 4. The spray granulation process adopted by the method of the present invention not only has high production efficiency, but also can achieve the regulation of the morphology and particle size of the composite ceramic powder by controlling the solid content of the slurry and the process parameters of the granulation process; in addition, the method of the present invention sinters and plasma spheroidizes the agglomerated powder obtained by spray granulation, thereby improving the bonding strength between small particles inside the agglomerated powder, improving the fluidity of the powder, and improving the density of the coating obtained by thermal spraying composite ceramic materials. Reduce the porosity of the coating and improve the mechanical properties, thereby solving the problem that the high-temperature electromagnetic functional coating is easy to fall off and fail in the actual use environment.

[0022] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings are only used for the purpose of illustrating specific embodiments and are not to be considered as limiting the present invention. In the entire drawings, the same reference symbols represent the same components; FIG1 is a SEM image of the composite ceramic powder 1 prepared in Example 1, (a) the overall appearance of the particle and (b) a partial enlarged view of the particle appearance; Figure 2 This is a SEM image of the composite ceramic powder 2 prepared in Example 2; Figure 3 This is a SEM image of the composite ceramic powder 3 prepared in Example 3; Figure 4 This is a SEM image of the composite ceramic powder 4 prepared in Comparative Example 1; Figure 5 This is a SEM image of the composite ceramic powder 5 prepared in Comparative Example 2; Figure 6 This is a SEM image of the composite ceramic powder 6 prepared in Comparative Example 3; Figure 7 This is a SEM image of the composite ceramic powder 7 prepared in Comparative Example 4; Figure 8 Environmental resistance test diagram of the electromagnetic functional composite coating 1 made by using the composite ceramic powder 1, (a) salt spray resistance, (b) solvent oil resistance; Fig. 9 The environmental resistance test diagram of the electromagnetic functional composite coating 2 made of the composite ceramic powder 2 is (a) salt spray resistance, (b) solvent oil resistance; Fig.10 Environmental resistance test diagram of electromagnetic functional composite coating 3 made of composite ceramic powder 3, (a) salt spray resistance, (b) solvent oil resistance; Fig.11 Environmental resistance test diagram of electromagnetic functional composite coating 4 made of composite ceramic powder 4, (a) salt spray resistance, (b) solvent oil resistance; Fig.12 Environmental resistance test diagram of electromagnetic functional composite coating 5 made of composite ceramic powder 5, (a) salt spray resistance, (b) solvent oil resistance; Fig.13 Environmental resistance test diagram of electromagnetic functional composite coating 6 made of composite ceramic powder 6, (a) salt spray resistance, (b) solvent oil resistance; Fig.14 Environmental resistance test diagram of the electromagnetic functional composite coating 7 made of composite ceramic powder 7, (a) salt spray resistance, (b) solvent oil resistance. DETAILED DESCRIPTION

[0024] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0025] With the increasingly widespread application of electromagnetic waves, higher requirements are placed on materials for shielding and absorbing electromagnetic waves. The application environment of electromagnetic functional materials is becoming more and more harsh. Because a single electromagnetic functional material and its loss mechanism limit its absorption performance of electromagnetic waves, people are committed to studying composite electromagnetic absorption materials composed of multiple electromagnetic functional materials to broaden the absorption band.

[0026] However, in practical applications, the electromagnetic functional coating composed of composite electromagnetic absorption materials has poor mechanical properties and low bonding strength (~6MPa). When the environment changes, including ambient temperature, medium and other factors, the coating is prone to cohesive fracture. Especially under harsh conditions of use, the coating is prone to problems such as shedding and failure, which affects the electromagnetic wave absorption efficiency and service life.

[0027] Therefore, the present invention provides a thermal spraying composite ceramic material, which includes a matrix material and a functional material, wherein the matrix material is one or more of mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride, and the functional material includes SiBCNFe or / and SiCuCN, Ti3SiC2 or / and TiC, CNTs or / and carbon fiber, MoSi2 or / and Si3N4, ZnO or / and MnO2, and YSZ.

[0028] According to some preferred embodiments of the present invention, the matrix material is mullite, and the functional materials include SiBCNFe, Ti3SiC2, CNTs, MoSi2, ZnO and YSZ.

[0029] The present invention evenly disperses a variety of electromagnetic functional materials into the matrix material. The various electromagnetic functional materials have a variety of loss mechanisms, broaden the electromagnetic wave absorption band, improve the absorption loss, and assume the controllability of the electromagnetic function, as shown in Table 2.

[0030] Specifically, SiBCNFe and SiCuCN have magnetic loss and dielectric loss mechanisms, CNTs and carbon fibers have resistive loss mechanisms, and Ti3SiC2, MoSi2, ZnO, TiC, Si3N4, AlN, and MnO2 have dielectric loss mechanisms.

[0031] The various electromagnetic functional materials described in the present invention are all temperature-resistant materials, which are conducive to the expansion of the preparation process and application environment of the composite ceramic material of the present invention. The composite ceramic powder material can be prepared by a spray granulation process, and the size, morphology and structure of the powder material can be controlled by adjusting the process parameters; the composite ceramic powder material can be sprayed and deposited onto the surface of the substrate at a certain speed by a thermal spraying process to improve the bonding strength with the substrate, achieve controllable coating thickness, simplify the coating preparation process, and reduce the impact on the substrate material.

[0032] Furthermore, the various electromagnetic functional materials used in the present invention cooperate and coordinate with each other to broaden the electromagnetic wave absorption band. In addition to limiting the composition of the composite ceramic material, the present invention also limits the content of each component.

[0033] According to some preferred embodiments of the present invention, the contents of the components in the composite ceramic material are, by mass percentage, SiBCNFe 8%-10%, Ti3SiC2 15%-18%, CNTs 2%-5%, MoSi2 5%-8%, ZnO 4%-6%, YSZ22%-27%, and the remainder mullite.

[0034] The composite ceramic material not only achieves the broadening of the electromagnetic wave absorption band by increasing the loss mechanism, but also takes into account that the different physical and chemical properties of different electromagnetic functional materials may affect the morphology, structure and performance of the composite ceramic material obtained after combination, thereby affecting its electromagnetic function and service life in practical applications.

[0035] It should be noted that in order for the absorbing material to absorb electromagnetic waves, it must meet impedance matching conditions and attenuation conditions. Impedance matching requires that the dielectric constant and magnetic permeability of the coating match within the entire frequency range to reduce the reflection of electromagnetic waves at the incident interface. When absorbers with multiple loss mechanisms constitute the composite absorber system of the present invention, a large number of interfaces and defects cause electromagnetic waves to be reflected and transmitted multiple times, thereby allowing as many waves as possible to enter the material body, thereby improving impedance matching and being beneficial to the absorption of electromagnetic waves.

[0036] It should be noted that the composite ceramic material of the present invention includes absorbing materials with different loss mechanisms, wherein the magnetic loss absorber mainly absorbs electromagnetic waves through a suitable magnetic permeability to generate magnetic loss; the dielectric loss absorber uses a suitable dielectric constant to absorb electromagnetic waves and generates dielectric loss; the resistive loss absorber converts electromagnetic wave energy into thermal energy loss through mechanisms such as electron clouds and lattice vibrations in the material; magnetic loss, dielectric loss and resistive loss do not exist in isolation, but are mutually synergistic and act together. The absorbers with different loss mechanisms form a complex electromagnetic field distribution in the coating, and the electromagnetic waves are affected by multiple loss mechanisms when propagating therein. This synergistic effect can significantly improve the absorbing performance of the coating, so that it can achieve high absorption rate in a wider frequency band. The proportion of magnetic loss, dielectric loss and resistive loss materials is accurately controlled to balance the contribution of dielectric loss, magnetic loss and resistive loss. Generally, the best combination of component ratios is found through experiments and simulations to achieve the best synergistic effect.

[0037] Specifically, the composite ceramic material of the present invention is a spherical powder with good fluidity and compactness, which is beneficial to reduce the porosity of the coating obtained by thermal spraying, increase the density of the coating, and improve the mechanical properties of the coating and the bonding strength between the coating and the substrate; the bulk density of the composite ceramic powder of the present invention is 0.4-2.2g / cm 3 , fluidity is 30-50s / 50g.

[0038] The present invention also limits the particle size of the spherical powder. The size and uniformity of the particle size will affect the density and bonding strength of the prepared coating. In the thermal spraying process of the material, the particle size will also affect the evaporation loss of the elements, thereby affecting the protective performance and service life of the coating.

[0039] Specifically, the particle size of the composite ceramic powder of the present invention is limited to 25-110 μm. If the particle size is too small, the fluidity of the powder is poor, and the evaporation loss of elements will increase, affecting the composition and density of the coating; if the particle size is too large, it is easy to cause the powder to be insufficiently melted in the high-temperature heat flow, affecting the deposition efficiency; in addition, the powder particle size distribution should not be too wide to avoid uneven heating of the powder during thermal spraying.

[0040] The present invention can adopt EDS, XRD, laser particle size analyzer, Hall flow meter, SEM and other testing technologies to characterize the composition and content, structure and performance of the thermal spraying composite ceramic material.

[0041] The present invention provides a method for preparing a thermal spraying composite ceramic material, the method comprising: (1) According to the composition of the composite ceramic material, a matrix raw material, a functional raw material, deionized water and a binder are mixed to obtain a mixed slurry; (2) spray granulating the mixed slurry to obtain agglomerated powder; (3) sintering the agglomerated powder; (4) The powder sintered in step (3) is subjected to plasma spheroidization treatment and sieved.

[0042] Specifically, in step (1), the mixing step is as follows: at room temperature, the raw materials are accurately weighed according to the mass ratio and placed in a stirring container, and then deionized water and a binder are added to the stirring container and stirred to obtain a uniformly mixed slurry.

[0043] Furthermore, the stirring speed is 100-150 rpm and the time is 5-7 h.

[0044] Furthermore, in order to control the morphology, density and forming and sintering properties of the particles obtained by subsequent spray granulation, it is necessary to limit the amount of deionized water and the amount of binder in the mixed slurry. Among them, the proportion of the binder should be appropriate to ensure that the viscosity of the slurry is moderate, which is conducive to the spheroidization and densification of the powder after granulation.

[0045] Specifically, the mass of deionized water in the mixed slurry of the present invention is 1-1.2 times the mass of the raw material; the mass of the binder is 0.5-1% of the mass of the raw material.

[0046] Furthermore, the binder of the present invention is compatible with the material, ensures a high powder output rate, does not affect the performance of the spray granulation process, and can be selected from one or more of polyvinyl alcohol, phenolic resin, polyacrylamide, and polypropylene. In view of the fact that polyvinyl alcohol also acts as a dispersant during the raw material mixing process, in some preferred embodiments of the present invention, the binder is polyvinyl alcohol.

[0047] The spray granulation process adopted by the method of the present invention not only has high production efficiency, but also can achieve regulation of the morphology and particle size of the obtained composite ceramic powder by controlling the solid content of the slurry and the process parameters of the granulation process.

[0048] Specifically, in step (2), the process parameters of the spray granulation of the present invention are as follows: inlet temperature 340-350°C, outlet temperature 100-110°C, spray disk speed 30-40Hz, and feed speed 35-45rpm.

[0049] Among them, the inlet and outlet temperatures of spray granulation affect the droplet drying efficiency and the performance of the separated material after drying. Too high a temperature will reduce the effect of the binder, affect the cohesive strength of the agglomerated powder, and easily cause the particles to be too fine; too low a temperature will easily cause wall sticking, and cause the powder particles to be insufficiently strong and easy to break.

[0050] In addition, the rotation speed of the spray disc will affect the atomization effect of the slurry and the particle size of the powder obtained. The faster the rotation speed, the smaller the atomized droplets and the higher the drying efficiency. The feed speed will affect the size of the droplets and the uniformity of the particles. For example, a feed speed that is too fast may cause the particles to be too large or irregular in shape; a feed speed that is too slow may cause the particles to be too small or stick together, and reduce production efficiency.

[0051] According to some preferred embodiments of the present invention, in the process parameters of the spray granulation, the inlet temperature is 340°C, 345°C or 350°C, the outlet temperature is 100°C, 105°C or 110°C, the spray disc speed is 30Hz, 35Hz or 40Hz, and the feed rate is 35rpm, 40rpm or 45rpm.

[0052] Furthermore, in order to improve the cohesive strength between small particles inside the agglomerated powder obtained by spray granulation, the present invention performs a sintering treatment on the agglomerated powder.

[0053] Specifically, in step (3), the specific steps of the sintering treatment are: placing the crucible containing the agglomerated powder in a sintering furnace, and sintering in a protective atmosphere: sintering at a temperature of 550-950°C for 2-4h; sintering at a temperature of 1100-1500°C for 2-5h; the present invention adopts sintering the agglomerated powder at high and low temperatures, which is beneficial to removing the binder and homogenizing the particles, better promoting the densification of the particles and improving the mechanical properties, and avoiding defects.

[0054] According to some preferred embodiments of the present invention, the sintering conditions are sintering at 950°C for 2h + sintering at 1100°C for 2h, or sintering at 950°C for 2h + sintering at 1150°C for 2h; or sintering at 950°C for 2h + sintering at 1200°C for 2h.

[0055] Furthermore, the present invention also performs plasma spheroidization treatment on the sintered agglomerated powder to improve the fluidity of the powder, and further improve the bonding strength between small particles inside the thermal spraying powder, improve the density of the coating made of thermal spraying composite ceramic material, reduce the porosity of the coating, and improve the mechanical properties of the coating.

[0056] Specifically, in step (4), the process parameters of the plasma spheroidization are: current 600-650A, main gas (Ar) 100-110SCFH, auxiliary gas (H2) 7-9SCFH, carrier gas (Ar) 8-10SCFH, powder feeding rate 2.0-3.0r / min.

[0057] According to some preferred embodiments of the present invention, the conditions for plasma spheroidization are: current 600A, main gas (Ar) 100SCFH, auxiliary gas (H2) 7SCFH, carrier gas (Ar) 8SCFH, and powder feeding rate 2.0r / min; or: current 625A, main gas (Ar) 105SCFH, auxiliary gas (H2) 8SCFH, carrier gas (Ar) 9SCFH, and powder feeding rate 2.5r / min; or: current 650A, main gas (Ar) 110SCFH, auxiliary gas (H2) 9SCFH, carrier gas (Ar) 10SCFH, and powder feeding rate 3.0r / min.

[0058] Furthermore, the method of the present invention also includes screening the agglomerated powder after spheroidization to obtain powder with a particle size and range that meet the requirements.

[0059] Specifically, the agglomerated powder is placed in an oscillating sieve analyzer, and the sieving parameters are: amplitude 2-3 mm, sieving time 3-5 min, and rest time 10 s, to obtain a thermal spray composite ceramic powder with a particle size range of 25-110 μm.

[0060] The present invention also provides a high-temperature electromagnetic functional coating, which includes a functional layer, and the material of the functional layer includes the above-mentioned thermal spray composite ceramic material. Specifically, the composite ceramic material is deposited on the surface of the substrate by a thermal spraying process as the functional layer of the electromagnetic functional coating. The prepared electromagnetic functional coating not only has a wider electromagnetic wave absorption bandwidth and larger absorption loss, but also has a lower porosity and a higher bonding strength with the substrate, thereby improving the mechanical properties of the coating and avoiding the existing electromagnetic functional coating from being easily cohesively fractured due to changes in the external environment, including factors such as ambient temperature and medium, and is prone to problems such as coating shedding and failure, especially under harsh conditions of use, which affects the electromagnetic wave absorption efficiency and service life.

[0061] Furthermore, the high-temperature electromagnetic functional coating also includes a bonding layer, a protective layer, and a surface layer.

[0062] Specifically, from the inside to the outside of the substrate surface, the composite coating specifically includes: a bonding layer, a protective layer, a functional layer and a surface layer, with thicknesses of 0.1-0.2mm, 0.03-0.05mm, 1.25-1.4mm and 0.05-0.1mm respectively, and the material of the functional layer contains a thermal sprayed composite ceramic material; wherein the composite ceramic material includes a matrix material and a plurality of electromagnetic functional materials dispersed in the matrix material.

[0063] The present invention limits the thickness of the bonding layer to 0.1-0.2 mm. If the bonding layer is too thin, it cannot play a role in transition of the thermal expansion coefficient, and the temperature resistance and thermal shock resistance of the coating system are reduced; if the bonding layer is too thick, it will cause the weight of the coating system to increase significantly and the surface density of the coating to increase.

[0064] The present invention limits the thickness of the protective layer to 0.03-0.05mm. If the protective layer is too thin, it cannot completely cover the bonding layer and cannot play a role in protecting the bonding layer, and the environmental resistance of the coating, such as salt spray resistance and solvent oil resistance, is reduced. Because the thermal expansion coefficient of the protective layer is relatively low, if the protective layer is too thick, it will cause the thermal expansion coefficient of the coating system to mismatch, and the temperature resistance and thermal shock resistance of the coating system will be reduced.

[0065] The present invention limits the thickness of the functional layer to 1.25-1.4 mm. If the functional layer is too thin, the electromagnetic function of the coating will be poor and the wave absorption performance will be poor. If the functional layer is too thick, although the maximum absorption loss will be increased, the wave absorption bandwidth will be reduced, and it will also cause the weight of the coating system to increase significantly and the surface density of the coating to increase.

[0066] The present invention limits the thickness of the surface layer to 0.05-0.1 mm. If the surface layer is too thin, it will not be able to completely cover the functional layer and cannot play a role in protecting the functional layer, and the environmental resistance of the coating, such as salt spray resistance and solvent oil resistance, will be reduced; if the surface layer is too thick, the weight of the coating system will be greatly increased, and the surface density of the coating will be increased.

[0067] The base material of the present invention is one of high temperature alloy and stainless steel.

[0068] Furthermore, from the inside to the outside of the substrate surface, the functional layer includes three layers: a first absorbing layer, a wave-transmitting layer and a second absorbing layer, wherein the materials of the first absorbing layer and the second absorbing layer are thermally sprayed composite ceramic materials.

[0069] The functional layer of the present invention has a trap-type structure, and electromagnetic waves are reflected and interfered multiple times inside the multi-layer structure, which increases the interaction time and number of electromagnetic waves with the material, thereby improving the absorption efficiency of electromagnetic waves and achieving multiple absorption of electromagnetic waves entering the coating inside the material.

[0070] The functional layer in the electromagnetic functional composite coating of the present invention has a three-layer trap structure, and a wave-transmitting layer is arranged between two wave-absorbing layers composed of composite ceramic materials, and the wave-transmitting layer can guide the electromagnetic waves initially attenuated by the second wave-absorbing layer to penetrate into the coating, and the first wave-absorbing layer further absorbs and attenuates the electromagnetic waves transmitted, thereby increasing the contact opportunities between the electromagnetic waves and the subsequent wave-absorbing layers, realizing multiple absorption of the electromagnetic waves entering the coating, and enhancing the wave-absorbing effect; through the combination of the multi-layer structure of the functional layer, the width of the coating absorption band is further widened, and the problem of the narrow absorption band of the high-temperature electromagnetic functional coating is better solved; in addition, the design of the wave-transmitting layer can also optimize the impedance matching between the materials, and further reduce the reflection loss of the electromagnetic waves on the interface. The thickness of each layer is limited, the weight of the coating is reduced, the bonding strength is improved, and it is easy to carry and install, and the application is broadened.

[0071] Furthermore, the material of the wave-transmitting layer should be resistant to high temperatures, have suitable electromagnetic parameters, and be able to transmit the electromagnetic waves that need to be absorbed. It can be one of alumina, mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride.

[0072] According to some preferred embodiments of the present invention, the material of the wave-transmitting layer is aluminum oxide.

[0073] The electromagnetic parameters of the thermal sprayed composite ceramic powder material were tested, and the CST software was used to calculate the simulated reflectivity of the three-layer structure of the electromagnetic functional layer. In the frequency range of 4-18GHz, the optimal aluminum oxide layer thickness was calculated to be 0.35-0.4mm.

[0074] Furthermore, in order to achieve effective bonding between the electromagnetic functional coating and the substrate material, the present invention adopts a material with good temperature resistance, good oxidation resistance and a suitable thermal expansion coefficient as a bonding layer, which not only achieves a firm bond between the substrate and the electromagnetic functional coating, but also reduces the difference in thermal expansion coefficients between the absorbing electromagnetic functional coating and the substrate in practical applications, thereby improving bonding strength and preventing the coating from falling off.

[0075] Specifically, the raw material constituting the bonding layer is metal alloy powder, selected from one or more of NiCrAlYSi, NiCrAlY, NiCrCoAlY, nickel-chromium alloy, and cobalt-chromium alloy.

[0076] According to a preferred embodiment of the present invention, the binder is NiCrAlYSi.

[0077] Furthermore, in order to prevent corrosive substances from entering the interior of the bonding layer, the bonding layer obtained by spraying is heat treated to form a dense metal oxide layer on the surface of the bonding layer, thereby preventing corrosive substances from entering the interior of the bonding layer through the pores and causing corrosion failure of the bonding layer.

[0078] Furthermore, in order to make the connection between the bonding layer and the electromagnetic functional coating more uniform and dense, and further prevent corrosive substances from entering the electromagnetic functional composite coating, the present invention uses a heat-resistant resin to spray and cure the bonding layer to form a protective layer to fill the pores and improve the density and mechanical properties of the coating.

[0079] Specifically, the heat-resistant resin constituting the protective layer has good compactness and excellent environmental resistance after curing, and can be selected from one or more of modified polysilazane resin, modified polysiloxane, modified siloxane, and modified silicone resin.

[0080] Furthermore, in order to isolate the electromagnetic functional layer from the external environment, prevent oxidation of the electromagnetic functional material under high temperature conditions, and improve the temperature resistance of the coating, the present invention uses a temperature-resistant and wave-transparent material to spray on the surface of the electromagnetic functional coating to form a surface layer located at the outermost layer of the composite coating; in addition, the surface layer can also further prevent corrosive substances from entering the electromagnetic functional composite coating.

[0081] Specifically, the material constituting the surface layer is an inert material with low oxygen permeability, a thermal expansion coefficient that matches well with the rest of the coating, and good phase structure stability, and no phase transition occurs in the working environment; it can be selected from high entropy rare earth disilicate (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7, mullite, BSAS (BaO-SrO-Al2O3-SiO2), alumina, and YSZ.

[0082] According to a preferred embodiment of the present invention, the material of the surface layer is high entropy rare earth disilicate (La 1 / 6 Hf 1 / 6Ta 1 / 6 Yb 1 / 6 Er 1 / 6 G 1 / 6 )2Si2O7.

[0083] The present invention adopts GJB 2038A-2011 standard, GB / T 5210 standard, GB / T 15749-1995 standard, GB / T 1771 standard and GB / T 9274 standard to test the electromagnetic function (absorption bandwidth, maximum absorption loss, etc.), temperature resistance, bonding strength, porosity and other properties of the electromagnetic functional composite coating.

[0084] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0085] Example 1 A method for preparing a thermal spray composite ceramic powder 1 comprises: (1) Weigh 160 g of SiBCNFe, 300 g of Ti3SiC2, 40 g of CNTs, 100 g of MoSi2, 80 g of ZnO, 440 g of YSZ, 880 g of mullite, 2000 g of deionized water, and 10 g of polyvinyl alcohol into a stirring container, and stir at a stirring speed of 100 r / min for 5 h to obtain a mixed slurry; (2) using a spray dryer to spray granulate the mixed slurry obtained in step (1), the spray granulation process parameters are: inlet temperature 340°C, outlet temperature 100°C, spray disk speed 30Hz, feed speed 35rpm, to obtain spherical agglomerated powder; (3) placing the spherical agglomerated powder in a crucible, and placing the crucible in an atmosphere sintering furnace for sintering. The sintering process is as follows: sintering at 950°C for 2 h, sintering at 1100°C for 2 h, and cooling in the furnace under an Ar protective atmosphere; (4) The sintered agglomerated powder is fed into a plasma spheroidization device. The process parameters of plasma spheroidization are: current 600A, main gas (Ar) 100SCFH, auxiliary gas (H2) 7SCFH, carrier gas (Ar) 8SCFH, and powder feeding rate 2.0r / min; (5) The spheroidized powder was placed in an oscillating sieving instrument for sieving. The sieving parameters were: amplitude 2 mm, sieving time 3 min, and rest time 10 s, to obtain a thermal sprayed composite ceramic powder 1.

[0086] The SEM photo of the thermal sprayed composite ceramic powder 1 is shown in FIG1 . As can be seen from FIG1 , the ceramic powder particles have good sphericity, a uniform and densified surface, no aggregation between the raw material particles inside the spherical powder, and the original particles of different particle sizes are evenly distributed in the spherical powder, indicating that the functional materials are evenly distributed in the matrix. After testing, the average particle size of the composite ceramic powder 1 is 80 μm, and the bulk density is 1.2 g / cm 3 , fluidity is 32s / 50g.

[0087] Example 2 A method for preparing a thermal spray composite ceramic powder 2 comprises: (1) Weigh 180 g of SiBCNFe, 330 g of Ti3SiC2, 70 g of CNTs, 130 g of MoSi2, 100 g of ZnO, 490 g of YSZ, 700 g of mullite, 2200 g of deionized water, and 15 g of polyvinyl alcohol, place them in a stirring container, and stir them at a stirring speed of 120 r / min for 6 h to obtain a mixed slurry; (2) using a spray dryer to spray granulate the mixed slurry obtained in step (1), the spray granulation process parameters are: inlet temperature 345°C, outlet temperature 105°C, spray disk speed 35Hz, feed speed 40rpm, to obtain spherical agglomerated powder; (3) placing the spherical agglomerated powder in a crucible, and placing the crucible in an atmosphere sintering furnace for sintering. The sintering process is as follows: sintering at 950°C for 2 h, sintering at 1150°C for 2 h, and cooling in the furnace under an Ar protective atmosphere; (4) The sintered agglomerated powder is fed into a plasma spheroidization device. The process parameters of plasma spheroidization are: current 625A, main gas (Ar) 105SCFH, auxiliary gas (H2) 8SCFH, carrier gas (Ar) 9SCFH, and powder feeding rate 2.5r / min; (5) The spheroidized powder was placed in an oscillating sieving instrument for sieving. The sieving parameters were: amplitude 2.5 mm, sieving time 4 min, and rest time 10 s, to obtain a thermal sprayed composite ceramic powder 2.

[0088] The SEM image of thermal sprayed composite ceramic powder 2 is shown in Figure 2 As shown in Figure 1, the ceramic powder particles have good sphericity, uniform surface and densification; after testing, the average particle size of the composite ceramic powder 2 is 82μm, and the bulk density is 1.5g / cm 3 , fluidity is 38s / 50g.

[0089] Example 3 A method for preparing a thermal spray composite ceramic powder 3 comprises: (1) Weigh 200 g of SiBCNFe, 360 g of Ti3SiC2, 100 g of CNTs, 160 g of MoSi2, 120 g of ZnO, 540 g of YSZ, 520 g of mullite, 2400 g of deionized water, and 20 g of polyvinyl alcohol and place them in a stirring container, stir at a stirring speed of 150 r / min for 7 h to obtain a mixed slurry; (2) using a spray dryer to spray granulate the mixed slurry obtained in step (1), the spray granulation process parameters are: inlet temperature 350° C., outlet temperature 110° C., spray disk speed 40 Hz, feed speed 45 rpm, to obtain spherical agglomerated powder; (3) placing the spherical agglomerated powder in a crucible, and placing the crucible in an atmosphere sintering furnace for sintering. The sintering process is as follows: sintering at 950°C for 2 h, sintering at 1200°C for 2 h, and cooling in the furnace under an Ar protective atmosphere; (4) The sintered agglomerated powder is fed into a plasma spheroidization device. The process parameters of plasma spheroidization are: current 650A, main gas (Ar) 110SCFH, auxiliary gas (H2) 9SCFH, carrier gas (Ar) 10SCFH, and powder feeding rate 3.0r / min; (5) The spheroidized powder was placed in an oscillating sieving instrument for sieving. The sieving parameters were: amplitude 3 mm, sieving time 5 min, and rest time 10 s, to obtain a thermal sprayed composite ceramic powder 3.

[0090] The SEM image of thermal sprayed composite ceramic powder 3 is shown in Figure 3As shown in Figure 1, the ceramic powder particles have good sphericity, uniform and dense surface; after testing, the average particle size of the composite ceramic powder 3 is 78 μm, and the bulk density is 2.0 g / cm 3 , fluidity is 42s / 50g.

[0091] Comparative Example 1 The thermal spraying composite ceramic powder 4 is prepared by the same method as in Example 2, except that: in step (1), 180 g of SiBCNFe, 400 g of Ti3SiC2, 130 g of MoSi2, 100 g of ZnO, 490 g of YSZ, 700 g of mullite, 2200 g of deionized water, and 15 g of polyvinyl alcohol are placed in a stirring container and stirred at a stirring speed of 120 r / min for 6 h to obtain a mixed slurry; and then steps (2) to (5) are performed to finally obtain the thermal spraying composite ceramic powder 4.

[0092] The SEM image of thermal sprayed composite ceramic powder 4 is shown in Figure 4 As shown in the figure, after testing, the average particle size of the composite ceramic powder 4 is 68 μm, and the bulk density is 3.0 g / cm 3 , fluidity 60s / 50g.

[0093] Comparative Example 2 The thermal spraying composite ceramic powder 5 is prepared by the same method as in Example 2, except that the spheroidization process in step (4) is not included in the preparation process, and the thermal spraying composite ceramic powder 5 is finally obtained.

[0094] The SEM photo of the thermal sprayed composite ceramic powder 5 is shown in FIG5 . After testing, it is found that the average particle size of the composite ceramic powder 5 is 65 μm and the bulk density is 1.1 g / cm 3 , fluidity 88s / 50g, powder surface is relatively rough.

[0095] Comparative Example 3 The thermal spraying composite ceramic powder 6 was prepared by the same method as in Example 2, except that: The sintering process in step (3) is: sintering at 450°C for 1 hour, sintering at 1000°C for 1 hour under Ar protective atmosphere, and cooling in the furnace; The plasma spheroidization process in step (4) is: current 550A, main gas (Ar) 85SCFH, auxiliary gas (H2) 5SCFH, carrier gas (Ar) 4SCFH, powder feeding rate 6r / min; finally, thermal spraying composite ceramic powder 6 is obtained.

[0096] The SEM photo of the thermal sprayed composite ceramic powder 6 is shown in FIG6 . After testing, it is found that the average particle size of the composite ceramic powder 6 is 66 μm and the bulk density is 3.1 g / cm3 , fluidity 66s / 50g, some areas of the powder surface are densified, while some areas are not densified.

[0097] Comparative Example 4 The thermal sprayed composite ceramic powder 7 was prepared by the same method as in Example 2, except that the spray granulation process parameters in step (2) were: inlet temperature 245°C, outlet temperature 115°C, spray disk speed 50 Hz, feed rate 60 rpm, and spherical agglomerated powder was obtained; finally, the thermal sprayed composite ceramic powder 7 was obtained.

[0098] The SEM photo of the thermal sprayed composite ceramic powder 7 is shown in FIG7 . After testing, it is found that the average particle size of the composite ceramic powder 7 is 60 μm and the bulk density is 3.4 g / cm 3 , the fluidity cannot be tested. The poor sphericity of the powder leads to poor fluidity, which in turn leads to unstable powder feeding during the spheroidization process. The powder surface is not completely densified after spheroidization, and the powder strength is low.

[0099] Application Example 1 The composite ceramic powder 1-7 prepared in Example 1-3 and Comparative Example 1-4 is used to prepare the functional layer of the high-temperature electromagnetic functional coating 1-7 by a thermal spraying process. The substrate material is a high-temperature alloy. From the inside to the outside of the substrate surface, the high-temperature electromagnetic functional coating includes a NiCrAlYSi bonding layer, a modified polysilazane resin protective layer, a functional layer and (La 1 / 6 Hf 1 / 6 Ta 1 / 6 Yb 1 / 6 Er 1 / 6Gd 1 / 6 )2Si2O7 surface layer, the thickness of each layer is as shown in Table 1; from the inside to the outside of the substrate surface, the functional layer includes a first absorbing layer, an alumina transparent layer and a second absorbing layer, the thickness of each layer is as shown in Table 1, wherein the materials of the first absorbing layer and the second absorbing layer are the above-mentioned composite ceramic powders respectively.

[0100] Table 1

[0101] The electromagnetic function, bonding strength, porosity, temperature resistance and environmental resistance of the high temperature electromagnetic functional coatings 1-7 were tested. When other conditions were the same, the test results were shown in Table 2. Figure 8-14 As shown, the performance test methods and standards are as follows: Coating electromagnetic function test: According to GJB 2038A-2011 standard, the test is carried out using the bow frame method, and the electromagnetic function of the material is measured based on the principle of reflection and absorption of electromagnetic waves on the material surface.

[0102] Pull-off adhesion: According to GB / T 5210 standard, the test column is bonded to the coating surface with adhesive, and then tensile stress is applied on a tensile testing machine to measure the tensile force required to destroy the adhesion unit area between the coating and the substrate, thereby evaluating the adhesion of the coating.

[0103] Coating porosity test: GB / T 15749-1995 standard uses the intercept method in the quantitative metallographic manual determination method to determine the porosity of the coating, that is, the pores in the coating are regarded as one phase, and the coating entity is regarded as one phase. The two-dimensional parameters measured in the metallographic grinding surface are used to infer the pore content in the three-dimensional space.

[0104] Salt spray resistance: According to GB / T 1771 standard, the salt spray test is carried out at (35±1)℃, 5%NaCl environment for 192 hours. After the test, take out the sample, wipe off the water marks / salt particles with absorbent cotton or soft paper, place it in the standard test environment for 30 minutes, and complete the appearance observation within 30 minutes.

[0105] Resistance to solvent oil: According to GB / T 9274 standard, immerse the coating in solvent oil and conduct medium resistance test at (23±2)℃ for 7 days. After the test, take out the sample and wipe off the oil stain with absorbent cotton or soft paper (120# solvent gasoline is allowed to be dipped to remove solvent oil residue). After placing it under standard test environment for 30 minutes, complete the appearance observation within 30 minutes.

[0106] Table 2

[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A thermal spraying composite ceramic material, characterized in that: The composite ceramic material includes a matrix material and a functional material, wherein the matrix material is at least one of mullite, zirconia, cordierite, silicon dioxide, silicon nitride, and boron nitride, and the functional material includes SiBCNFe or / and SiCuCN, Ti3SiC2 or / and TiC, CNTs or / and carbon fiber, MoSi2 or / and Si3N4, ZnO or / and MnO2, and YSZ; the functional material is uniformly dispersed in the matrix material.

2. The composite ceramic material according to claim 1, characterized in that: Calculated by mass percentage, the contents of the components in the composite ceramic material are: SiBCNFe 8%-10%, Ti3SiC2 15%-18%, CNTs 2%-5%, MoSi2 5%-8%, ZnO 4%-6%, YSZ 22%-27%, and the balance mullite.

3. The composite ceramic material according to claim 1, characterized in that: The composite ceramic material is spherical powder with a particle size of 25-110 μm.

4. The composite ceramic material according to claim 3, characterized in that: The bulk density of the spherical powder is 0.4-2.2 g / cm 3 , fluidity is 30-50s / 50g.

5. A method for preparing the composite ceramic material according to any one of claims 1 to 4, characterized in that: The method comprises: (1) According to the composition of the composite ceramic material, a matrix raw material, a functional raw material, deionized water and a binder are mixed to obtain a mixed slurry; (2) spray granulating the mixed slurry to obtain agglomerated powder; (3) sintering the agglomerated powder; (4) The powder sintered in step (3) is subjected to plasma spheroidization treatment and sieved.

6. The method according to claim 5, characterized in that In step (1), the mass of deionized water is 1-1.2 times the mass of the raw material; And / or, the mass of the binder is 0.5-1% of the mass of the raw material.

7. The method according to claim 5, characterized in that In step (2), the process parameters of the spray granulation are: inlet temperature 340-350°C, outlet temperature 100-110°C, spray disk speed 30-40Hz, and feed speed 35-45rpm.

8. The method according to claim 5, characterized in that In step (3), the sintering process parameters are: sintering at 550-950°C for 2-4h under protective atmosphere; sintering at 1100-1500°C for 2-5h.

9. The method according to claim 5, characterized in that In step (4), the process parameters of the plasma spheroidization treatment are: current 600-650A, main gas Ar 100-110SCFH, auxiliary gas H2 7-9SCFH, carrier gas Ar 8-10SCFH, powder feeding rate 2.0-3.0r / min.

10. A high temperature electromagnetic functional coating, characterized in that: The high-temperature electromagnetic functional coating comprises a functional layer, and the material of the functional layer comprises the thermal spraying composite ceramic material according to any one of claims 1 to 4 or the thermal spraying composite ceramic material obtained by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • Nano ceramic electromagnetic oven panel and preparation method thereof

    CN101191624A

  • Preparation method of SiCn-MoSi2-mullite composite overcoating for C / C composite material

    CN102674891A

  • Preparation method of spherical ZrO2 powder

    CN111960465A

  • Method for preparing intermediate layer of environmental barrier coating by using TiC modified mullite

    CN114262216A

  • Caron nanotube / mullite ceramic base multiple phase material and preparation method thereof

    CN1669982A